2019
DOI: 10.1111/ijn.12754
|View full text |Cite
|
Sign up to set email alerts
|

The health‐related quality of life of nursing workers: A cross‐sectional study in medical institutions

Abstract: Aims This study aimed to evaluate the health‐related quality of life of nursing workers and influential factors. Background Nursing workers are under great occupational stress. However, few population‐level studies of nursing workers' health conditions have been reported from China. Design This was a cross‐sectional study conducted in 12 medical institutions in east China between January and March 2015. Methods Social‐demographic information, nursing workers' work‐related information and health‐related quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The life–work design deals with the composition of the work and identifies the actual work responsibilities. For instance, the availability of work tasks, security, education, staffing ratios, and individual success are part of the quality of the work–life equation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The life–work design deals with the composition of the work and identifies the actual work responsibilities. For instance, the availability of work tasks, security, education, staffing ratios, and individual success are part of the quality of the work–life equation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has evaluated the impact of QWL on healthcare professionals [ 2 , 4 , 7 , 11 , 12 , 14 , 15 , 16 ]. However, no studies have dealt with QWL levels for Magnetic Resonance Imaging Technologists (MRITs) in the Kingdom of Saudi Arabia (KSA).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of designing the questionnaire, we collected as much as possible the basic information of the subjects and the variables information that may affect mental status of medical workers during COVID-19. Studies have shown that the measurable factors affecting mental status mainly include the five respects of demography (33,34), family (35,36), employment (37,38), lifestyle (39,40), and work/living environment related to COVID-19 (41,42). Based on the results of the existing literature and the actual situation of medical workers during COVID-19, 32 factors were decided.…”
Section: Data Preparationmentioning
confidence: 99%
“…The life-work design deals with the composition of the work and identi es the actual work being done. For instance, the availability of supplies, work tasks, security, education, sta ng ratios, and individual success are parts of the quality of the work-life equation 11 .…”
Section: Control At Work and Home-work Interfacementioning
confidence: 99%